2020
DOI: 10.1021/acs.est.9b04989
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Polyfluoroalkyl Surfactants on Surface Soils: Effect of Molecular Structures, Soil Properties, and Solution Chemistry

Abstract: Zwitterionic, cationic, and anionic per-and polyfluoroalkyl substances (PFASs) are identified in aqueous film-forming foam (AFFF) concentrates and AFFF-impacted sites. However, the mobility potential of zwitterionic and cationic PFASs is poorly understood, preventing reliable site assessment. The study aimed to elucidate the mobility behaviors of PFASs of various charge states in saturated soil−water systems and assess critical influencing factors. Five anionic, three zwitterionic, and one cationic PFASs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 45 publications
8
94
4
Order By: Relevance
“…We recognize that foc in the first meter below the land surface may be much greater than the foc employed in the present study. Additionally, more complex sorption processes such as electrostatic interactions may lead to enhanced solid-phase adsorption in particular for cationic and zwitterionic PFAS (Barzen-Hanson et al, 2017;Mejia-Avendaño et al, 2020;Nickerson et al, 2020;Xiao et al, 2019). Under these conditions, our simulations would overestimate PFAS leaching.…”
Section: Discussionmentioning
confidence: 99%
“…We recognize that foc in the first meter below the land surface may be much greater than the foc employed in the present study. Additionally, more complex sorption processes such as electrostatic interactions may lead to enhanced solid-phase adsorption in particular for cationic and zwitterionic PFAS (Barzen-Hanson et al, 2017;Mejia-Avendaño et al, 2020;Nickerson et al, 2020;Xiao et al, 2019). Under these conditions, our simulations would overestimate PFAS leaching.…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which soil was characterized differed widely between the studies and, while not all of the measured parameters are recorded here, effort was made to record those that were common to multiple studies or indicated by prior research to influence PFAS sorption. These properties included concentration of PFAS in solution, pH of aqueous and solid phases, soil composition (sand, silt, clay), percent organic carbon, soil concentrations of K, Ca, Mg, Na, Fe, and Al, cation exchange capacity (CEC), and anion exchange capacity (AEC) (Ahrens et al 2011;Anderson et al 2019;Campos Pereira et al 2018;Ferrey et al 2012;Higgins and Luthy 2006;Jeon et al 2011;Knight et al 2019;Li et al 2018;Milinovic et al 2015;Mejia-Avendaño et al 2020;Oliver et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the frequently encountered chlorinated solvents like tetrachloroethylene (PCE), trichloroethylene (TCE), and 1,1,1-trichloroethane (1,1,1-TCA) are neutral, hydrophobic organic compounds and sorption is expected to be a function of the OC content in sediments and soils, with only limited interaction with mineral surfaces (Allen-King et al 1997;Lu et al 2011). This approach was initially applied to PFAS chemicals as well; however, studies suggest that a wide range of sorption mechanisms are important in environmental systems (Johnson et al 2007;Ferrey et al 2012;Guelfo and Higgins 2013;Chen et al 2016;Barzen-Hanson et al 2017;Hale et al 2017;Dalahmeh et al 2018;Anderson et al 2019;Brusseau 2019;Mejia-Avendaño et al 2020;Oliver et al 2020). The characteristic C-F chain moiety of PFAS molecules results in strong hydrophobicity and expected interaction with the organic matter fraction of soils (Li et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The organic matter is typically negatively charged and enhances the release of anionic hydrophobic organic contaminants such as PFAS and polycyclic aromatic hydrocarbons (PAHs) owing to electrostatic repulsion. However, electrostatic attraction of PFAS occurs at low pH of soil medium with small organic carbon content [50]. Furthermore, the PFAS adsorption onto organic matter occurs due to hydrophobic interactions for larger retention of PFAS in soil [51].…”
Section: Role Of Soils In the Sequestration Of Contaminantsmentioning
confidence: 99%